Comparison of basic lab test results with more sophisticated lab and In Situ test mothods on soils in southeastern Wisconsin - Li, Lin; Edil, Tuncer; Benson, Craig H.; Camargo, Felipe F.; Mickelson, David (Wisconsin Highway Research Program, 2009)
This report describes a comparison of basic laboratory test results with more sophisticated laboratory and in situ tests methods on soils in Southeastern Wisconsin. The generated soils data in the Milwaukee Marquette Interchange project has been used in an attempt to correlate the more ?routine? laboratory tests to determine geotechnical design parameters (such as phiangle, cohesion, unit weight, unconfined compression, consolidation characteristics, etc.).
71 p.
Keywords: Soil tests; Field tests; Laboratory tests